Pengaruh Platfrom E-Commerce Terhadap Perilaku Konsumen Gen-Z: Studi Kasus Prodi Ekonomi Universitas Nurul Jadid - Deddy Junaedi; Fadhillatus Sholihah; Dini Fitriani Ali; Dita Wulandari Agustin; Dia Auliatur Rohmah (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
With a case study focus on students of the Economics Study Program at Nurul Jadid University, this research seeks to examine how e-commerce platforms influence the purchasing habits of Generation Z. As digital natives, Generation Z is highly influenced by digital technology, including e-commerce platforms, which influence their consumption habits and purchasing choices. This research combines research data from secondary sources, such as literature, with qualitative methodologies study. This study's method of gathering data is a literature review. According to research findings, Gen-Z customer behavior is highly influenced by e-commerce platform features including user ratings, promotions, ease of access, and flexible payment options. The accessibility and attractiveness of platform promotions are key determinants of consumption behavior. These results have significant consequences for e-commerce players looking to improve marketing tactics and attract Gen-Z customers.